Implementasi Balance Scorecard Dalam Analisis Kinerja Rumah Sakit Di Indonesia - Vip Paramarta; Suwoko Tya Wicaksono; Nina Risnawaty; Ida Ayu Triana; Arnita Niroha Halawa; Intan Permatasari (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
Hospital is a health service organization that organizes complete individual health services, and provides inpatient, outpatient and emergency services. In order for hospital management to run well, it is necessary to measure hospital performance, namely the Balanced Scorecard method. : The Balanced Scorecard (BSC) is used as a decision-making tool regarding the actions that must be taken to correct deficiencies and advance the hospital. Purpose: This study aims to determine the application of the balanced scorecard (BSC) in analyzing the performance of hospitals in Indonesia. Methods: This study used the library research method. . Results: a literature review of ten journals shows that all conclude that localization and conceptual use of the BSC can greatly improve hospital performance. The results of performance analysis with the BSC at the hospital can also provide clear direction in determining policies, resources and routine activities, as well as in building systems in each unit in the hospital. Conclusion: BSC can not only be applied in private hospitals, but government hospitals also need to apply BSC to measure their performance and be used as a guide in making policies and designs or work plans. Findings from existing studies must also be enriched by the literature and by empirical evidence about the benefits of BSC application in hospitals. It will also provide experience for a number of hospitals in Indonesia which can be a reference for expanding the implementation of BSC in hospital administration.